Simulation of Cutting Particles Transportation in Oil Well Drilling - Eltilib, R. A E. E. (2009)
In the well drilling process, much of expensive information would be studied and possible practical recommendations could be forwarded if appropriate modelling of the well cleaning is developed to simulate the cuttings transportation at different well-pipe geometries, orientations, mud properties, and cutting particles properties. This study target to understand and investigate the transport phenomena in the three drilling orientations: horizontal, inclined and vertical using actual mud and drilled cuttings condition. The model build up is started, as presented here, from Single-phase annular flow to understand the primary annular flow affecting variables, and then the study will extend to get the multi-phase annular flow. The developed model indicates that the variables responsible to calculate the annular velocity are: fluid density, fluid viscosity, drill-pipe & annulus size and pressure gradient. As a second step in the model the build up, appropriate representation for the viscoelastic mud nature, and for the pressure gradient were suggested to develop the model closer to the actual drilling cleaning process.